RESEARCH ON THE CALCULATION MODEL OF DENT WITHOUT CONCAVE ANGLE ON OIL AND GAS PIPELINE - LI ChengBing; DANG SiHong (Jixie qiangdu)
The most common type of pipe mechanical damage is dent defect,which is a major cause of leading to pipeline fatigue rupture. For further research on the security of the pipelines,it is necessary to establish a calculation model serving actual conditions. Predecessors have carried on the comprehensive analysis of dent with concave angle by stick model and spherical model. A distinguishing method between dent with concave angle and without concave angle is proposed in this paper,The online detection data of pipeline shows that the dent without concave angle is in the majority. Then calculation model of dents without concave angle—hoop stick model is presented,which is verified by Finite Element simulating the actual dimension.Finally,influence of the stick parameters to result of the dent simulation is studied. It turns out that the simulation of differentsized dents without concave angle can be achieved by changing the curvature radius of hoop stick. Further research also showed that dent without concave angle on pipeline safety cannot be ignored.